Propagation of the endangered Azorean cherry Prunus azorica using stem cuttings and air layering - Moreira, Orlanda (2010)
Prunus azorica (Hort. ex Mouillef.) Rivas Mart., Lousã, Fern. Prieto, E. Dias, J.C. Costa & C. Aguiar is an endangered tree endemic to the Azores, with an ecological and ornamental interest. The objective of this study was to determine the conditions necessary for the successful propagation of P. azorica by stem cuttings and air-layering. Stem cuttings collected in March with two apical leaf pairs pruned to 1/3 of their leaf area were submitted to different treatments, including a basal split wound, two rooting mixtures, namely, perlite and peat (1:1) or perlite and natural soil (1:1), and dipping of the base in indole-3-butyric acid (IBA) solution at four concentrations (0, 2500, 5000 or 7000 mg/L). After eight weeks 75% rooting was achieved with 75 to 88% survival, without addition of IBA and with split wound using both substrate mixtures. Air layering was conducted in June in branches of adult trees with the addition of 0, 2500 or 3000 mg/L of IBA. After 12 months 100% rooting and survival was recorded in all treatments. Our study thus indicates that P. azorica is a taxon amenable for vegetative propagation by stem cuttings and air layering without requiring addition of IBA to induce rooting. Both methods should be used in order to recover natural populations, when seeds are not available or are available in reduced amounts.